Guidelines for the master's thesis by students majoring in 122 "Computer Science" - Kopp, Andrii Mykhailovych; Cherednichenko, Olga Yuriivna; Shmatko, Oleksandr Vitaliyovych; Litvinova, Uliya Sergiivna; Ivashchenko, Oksana Vitaliivna (National Technical University "Kharkiv Polytechnic Institute", 2025)
A master's qualifying work is a completed independent and original work that contains a set of research results and scientific positions that the author defends publicly. Such a work must have internal unity, which testifies to the author's personal contribution and ability to conduct independent research, using theoretical knowledge and practical skills. Violations of the ethics of scientific research are unacceptable in a master's thesis, including: falsification of scientific data, incorrect borrowings, violation of the rules of scientific citation, misappropriation of other people's scientific ideas, distortion of scientific facts and ideas of other researchers and the results of one's own research, use of unscientific and academically questionable sources of information, etc. The content of the work may consist of the results of theoretical and experimental research, development of new technologies, methodological techniques and methods for solving scientific problems in the field of information technology, as well as their theoretical justification. The master's thesis should demonstrate the author's ability to conduct scientific research independently, using theoretical knowledge and practical skills, to see professional problems, to be able to formulate research tasks, select methods for solving them, plan, organize and conduct research, interpret its results and formulate conclusions. These guidelines define the general requirements for a master's thesis, its approximate subject matter and structure, the rules of formatting and the procedure for preparing the work for defense.
Keywords: guidelines; information technology; software; requirements for writing a master's thesis; requirements for the explanatory note; defending a master's thesis